Development of a cognitive behavioral therapy-based bicultural-bilingual identity-informed psychoeducation for deaf young adults - Tayone, Reianne Patrick M.
This study aimed to develop and evaluate a manualized, eight-session, bi-weekly Cognitive-Behavioral Therapy (CBT)-based psychoeducation program tailored to the unique needs of deaf young adults in the Philippines. A pre-intervention survey (n=48) revealed that communication and relationship challenges with their deaf peers were prevalent mental health concerns. Moreover, the majority of participants (52%) were Deaf acculturated, while bicultural identity integration among the sample was moderate. Based on these findings, an eight-session, bi-weekly program was developed and implemented with six participants. Thematic analysis of intervention narratives confirmed the identified mental health concerns and highlighted the significance of family, community, and self-support for Deaf individuals. A Wilcoxon signed rank test was conducted to assess changes in intervention participants' scores on the Deaf Acculturation Scale (DAS) and the Bicultural Identity Integration (BII) scale. Results indicated a significant increase in DAS scores (Z=-2.201, p=0.028), suggesting a strengthening of Deaf identity. However, inconclusive results were obtained for the BII due to a limited sample size. This study contributes to the understanding of the mental health experiences of deaf young adults in the Philippines and underscores the importance of culturally sensitive interventions. Recommendations for future research, intervention, and policy include conducting efficacy studies on counseling interventions for Deaf individuals, investigating Deaf identity in the Philippine context, and advocating for increased access to mental health services for Deaf individuals.